IGNEOUS GRAPHITE IN ENSTATITE CHONDRITES - Rubin A.E. (My University, 1997)
Igneous graphite, a rare constituent in terrestrial mafic and ultramafic rocks, occurs in three EH and one EL enstatite chondrite impact-melt breccias as 2-150 mu m long euhedral laths, some with pyramidal terminations. In contrast, graphite in most enstatite chondrites exsolved from metallic Fe-Ni as polygonal, rounded or irregular aggregates. Literature data for five EH chondrites on C combusting at high temperatures show that Abee contains the most homogeneous C isotopes (i.e. delta(13)C = -8.1 +/- 2.1%); in addition, Abee's mean delta(13)C value is the same as the average high-temperature C value for the set of five EH chondrites. This suggests that Abee scavenged C from a plurality of sources on its parent body and homogenized the C during a large-scale melting event. Whereas igneous graphite in terrestrial rocks typically forms at relatively high pressure and only moderately low oxygen fugacity (e.g., similar to 5 kbar, logf(O2) similar to -10 at 1200 degrees C), igneous graphite in asteroidal meteorites formed at much lower pressures and oxygen fugacities.